(untitled) (Salud, Arte y Cuidado, 2018)
The Ohdo blepharophimosis syndrome is constituted by multiple congenital malformations, among them; Blepharophimosis, palpebral ptosis and dental hypoplasia, as well as retarded growth, intellectual and auditory disability. We present the case of an 11 - year - old schoolgirl with facial dysmorphia, including Blepharophimosis and Cleft Palate. It also presents antecedents of congenital heart disease and global developmental delay, of apparently healthy parents, who deny isonimia. The findings are discussed and the characteristics of the patient compared to the literature are compared. Fewer than 30 patients have been described worldwide, making the diagnosis of this syndrome an interesting finding. Diagnostic suspicion in intrauterine or early life is essential to reduce the impact on quality and life expectancy of patients, the importance of making an early diagnosis leads timely to relevant genetic and multidisciplinary advice.